2016
DOI: 10.3390/ijms17111794
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Proteomic and Physiological Analysis Reveals the Variation Mechanisms of Leaf Coloration and Carbon Fixation in a Xantha Mutant of Ginkgo biloba L.

Abstract: Yellow-green leaf mutants are common in higher plants, and these non-lethal chlorophyll-deficient mutants are ideal materials for research on photosynthesis and plant development. A novel xantha mutant of Ginkgo biloba displaying yellow-colour leaves (YL) and green-colour leaves (GL) was identified in this study. The chlorophyll content of YL was remarkably lower than that in GL. The chloroplast ultrastructure revealed that YL had less dense thylakoid lamellae, a looser structure and fewer starch grains than G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 88 publications
5
27
0
Order By: Relevance
“…reported that spectral optical properties change due to retention of carotenoids in yellow leaves in the autumn. Recently, Liu et al 12 analyzed the proteomic profiles of yellow and green G. biloba leaves and identified differentially accumulated proteins involved in energy metabolism, photosynthesis and carbon fixation. To better understand the mechanism of coloration and color variation in G. biloba leaves, it is important to compare yellow mutant leaves with green leaves under the same spatiotemporal and developmental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…reported that spectral optical properties change due to retention of carotenoids in yellow leaves in the autumn. Recently, Liu et al 12 analyzed the proteomic profiles of yellow and green G. biloba leaves and identified differentially accumulated proteins involved in energy metabolism, photosynthesis and carbon fixation. To better understand the mechanism of coloration and color variation in G. biloba leaves, it is important to compare yellow mutant leaves with green leaves under the same spatiotemporal and developmental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Chlorophyll (Chl) is an extremely important pigment that absorbs and converts light energy for plant use (Sandonà et al1998). In Chldeficient mutants, a strong decrease or increase occurs in the abundance of the proteins involved in various metabolic pathways, including Chl biosynthesis and degradation metabolism, nitrogen metabolism, chloroplast development, and carbon and energy metabolism (Rutschow et al 2008, Liu et al 2016. For example, in the Arabidopsis ffc mutant (pale green), the levels of lightharvesting complex I (LHCI) and light-harvesting com-plex II (LHCII) antennae proteins and stromal chaperones (Cpn60, Cpn21, and Hsp70) increased, while the levels of chloroplast-encoded PSII core complex proteins (D1, D2, CP43, CP47, and cytochrome b559α) and nucleus-encoded proteins (OEC16, OEC23, and OEC33) decreased (Rutschow et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…APX and SOD are the key enzymes catalyzing the conversion of H2O2 to H2O. This indicates that the mutant is more sensitive to photoinduced damage and ROS accumulation (Liu et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…using two-dimensional gel electrophoresis (2-DE) and MALDI-TOF mass spectrometry. Liu et al [ 13 ] provide new insights into the molecular regulation of leaf color variation and carbon fixation in a xantha mutant of Ginkgo biloba L. by exploiting 2-DE coupled with MALDI-TOF/TOF mass spectrometry. Yu et al [ 14 ] present comparative proteomic analysis of chimera Hosta “Gold Standard” leaves from various regions at different development stages and under excess nitrogen fertilization using 2-DE coupled MALDI-TOF/TOF MS.…”
mentioning
confidence: 99%